2014
DOI: 10.11607/ijp.3847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occlusal Rest Design on Pressure Distribution Beneath the Denture Base of a Distal Extension Removable Partial Denture—An In Vivo Study

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The authors explained that such results may be attributed to the fact that the loaded point moved to the thinnest portion (the most protruded point of occlusal rest base). Although minority of scientific studies are dealing with the occlusal rest biomechanical behavior, it may be, however, stated that stress distribution on the residual ridge beneath the RPD base is dependent on the occlusal rest design [17].…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained that such results may be attributed to the fact that the loaded point moved to the thinnest portion (the most protruded point of occlusal rest base). Although minority of scientific studies are dealing with the occlusal rest biomechanical behavior, it may be, however, stated that stress distribution on the residual ridge beneath the RPD base is dependent on the occlusal rest design [17].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the occlusal forces exerted on an RPD are transmitted to the abutment tooth primarily through the occlusal rest. Another study looked into the effect of long and short guide planes and plates in force transmission, and found no difference between them . However, Ahmad et al demonstrated that guiding planes offer some frictional resistance to RPD displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving maximum support from suitable abutment teeth is a key factor in the fabrication of RPDs . Rests are the primary RPD components incorporated and designed to provide adequate support and favorable transmission of forces to the abutment teeth . Several studies have looked at commonly used clasp assembly designs, clasp component function, number of clasps, and retention .…”
mentioning
confidence: 99%
“…b). These diverse patterns in Group 2 may depend on the design of RPD , shape of residual ridge , free‐end saddle length , condition of opposite dentition, occlusal condition, hours of RPD use, etc. Furthermore, there are many additional reasons to effect bone metabolism, such as diet, calcium and hydroxyapatite balance and hormones.…”
Section: Discussionmentioning
confidence: 99%